1367 Five Years of Robotic Surgery in Colorectal Service: James Cook University Hospital Experience. (12th October 2021) - France, K; Aradaib, M; Jha, M
Abstract: Aim: This paper gives an account of our institutional experience with safe adoption of robotic surgery in colorectal service. Method: Analysis of our prospectively maintained database of all patients who underwent robotic colorectal surgery in our institute between February 2015 and February 2020. Overall surgical and oncological outcomes were interrogated. Results: A total of 255 patients underwent robotic surgery between 2015 and 2020. 148 were males, and 107 were females. Median age was 68 years (range: 35–89). 198 patients had bowel cancer and 57 had benign conditions. Operative procedures performed were anterior resection (n = 125), right colectomy (n = 77), abdominoperineal resection (n = 40), subtotal colectomy (n = 5), completion proctocolectomy (n = 2) and reversal of Hartmann's procedure (n = 6). Mean operative time was 164 (SD ± 47.5) for right colectomy and 267 (SD ± 77.8) for anterior resection. Median length of hospital stay was 6 days (IQR: 4 – 9). There was no 30 days mortality or intraoperative complications. Conversion to open or laparoscopy surgery rate was 5.1% (n = 13). Anastomotic leakage occurred in 3 patients (1.2%). Median lymph nodes harvested were 21 (range 4 – 79) and the R0 resection rate was 96.5%. Conclusions: Our results demonstrate that colorectal robotic surgery is feasible and can be adopted safely for both benign and neoplastic conditions without undermining clinical or oncological outcomes.